2004
DOI: 10.1128/jcm.42.5.2134-2143.2004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of Multiple Staphylococcal Enterotoxin Genes by an Oligonucleotide Microarray Assay

Abstract: Staphylococcal enterotoxins (SEs) are a family of 17 major serological types of heat-stable enterotoxins that are one of the leading causes of gastroenteritis resulting from consumption of contaminated food. SEs are considered potential bioweapons. Many Staphylococcus aureus isolates contain multiple SEs. Because of the large number of SEs, serological typing and PCR typing are laborious and time-consuming. Furthermore, serological typing may not always be practical because of antigenic similarities among ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 40 publications
3
35
1
2
Order By: Relevance
“…It was also shown that all MRSA strains harbored SGF, SGFa and SGFb prophage types; therefore, the presence of sea, sek and seq genes was not surprising. This finding was not in agreement with those of other studies, in which the prevalence of these genes was significantly lower (12,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). On the other hand, the high prevalence of sea, sek and seq genes was shown in MRSA strains isolated from patients in a referral hospital in Tehran, Iran (42).…”
Section: Discussioncontrasting
confidence: 55%
“…It was also shown that all MRSA strains harbored SGF, SGFa and SGFb prophage types; therefore, the presence of sea, sek and seq genes was not surprising. This finding was not in agreement with those of other studies, in which the prevalence of these genes was significantly lower (12,15,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). On the other hand, the high prevalence of sea, sek and seq genes was shown in MRSA strains isolated from patients in a referral hospital in Tehran, Iran (42).…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, genes of the egc cluster were found in isolates recovered from nasal and blood specimens in high percentages (4,5). Recently, by applying the microarray technology for simultaneous detection of the SE genes, Sergeev et al (34) estimated that about 92% of S. aureus strains contain multiple SE genes (especially the egc cluster genes). Surveys of the egc distribution in S. aureus strains of animal origin also demonstrated a high frequency of egc-like genes (36).…”
Section: Resultsmentioning
confidence: 99%
“…Microarray technologies have become a tool of choice for multiparametric diagnostic assays and for gene expression profiling (7,14,21,24). The ability to perform sensitive and reproducible microarray hybridizations depends to a great extent on the quality of the microarray substrate.…”
Section: Discussionmentioning
confidence: 99%